Household coverage of Swaziland's national community health worker programme: a cross-sectional population-based study - Geldsetzer, Pascal; Vaikath, Maria; De Neve, Jan-Walter; Bossert, Thomas John; Sibandze, Sibusiso; Bärnighausen, Till (Tropical medicine & international health, 2017)
Objectives To ascertain household coverage achieved by Swaziland's national community health worker (CHW) programme and differences in household coverage across clients’ sociodemographic characteristics. Methods Household survey from June to September 2015 in two of Swaziland's four administrative regions using two-stage cluster random sampling. Interviewers administered a questionnaire to all household members in 1542 households across 85 census enumeration areas. Results While the CHW programme aims to cover all households in the country, only 44.5% (95% confidence interval: 38.0% to 51.1%) reported that they had ever been visited by a CHW. In both uni- and multivariable regressions, coverage was negatively associated with household wealth (OR for most vs. least wealthy quartile: 0.30 [0.16 to 0.58], P < 0.001) and education (OR for >secondary schooling vs. no schooling: 0.65 [0.47 to 0.90], P = 0.009), and positively associated with residing in a rural area (OR: 2.95 [1.77 to 4.91], P < 0.001). Coverage varied widely between census enumeration areas. Conclusions Swaziland's national CHW programme is falling far short of its coverage goal. To improve coverage, the programme would likely need to recruit additional CHWs and/or assign more households to each CHW. Alternatively, changing the programme's ambitious coverage goal to visiting only certain types of households would likely reduce existing arbitrary differences in coverage between households and communities. This study highlights the need to evaluate and reform large long-standing CHW programmes in sub-Saharan Africa.